2000
DOI: 10.1063/1.125826
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional growth of InSb thin films on GaAs(111)A substrates

Abstract: Heteroepitaxy of high-quality InSb films was performed directly on GaAs surfaces by using molecular beam epitaxy. Despite the 14.6% lattice mismatch, two-dimensionally grown InSb on GaAs(111)A substrates were obtained from the initial stage, but not on (001) substrates. A conductive layer was formed from the early stage of the growth on the (111)A surface, and the mobilities and carrier concentrations of InSb on (111)A substrates suggested a low defect density due to confinement of the dislocations to the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
43
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 17 publications
(5 reference statements)
6
43
1
Order By: Relevance
“…The ͑111͒A growth suppresses edge dislocations which are thought to be responsible for the increase of n at the interface. 12 The lower apparent, i.e., experimentally measured, n from the Imperial ͑100͒ growth suggests a lower density of such dislocations, which is consistent with the improved mobility. Note that there is surface depletion because the Fermi level is known to be pinned close to the valence band edge at the surface of the material.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…The ͑111͒A growth suppresses edge dislocations which are thought to be responsible for the increase of n at the interface. 12 The lower apparent, i.e., experimentally measured, n from the Imperial ͑100͒ growth suggests a lower density of such dislocations, which is consistent with the improved mobility. Note that there is surface depletion because the Fermi level is known to be pinned close to the valence band edge at the surface of the material.…”
supporting
confidence: 66%
“…This is consistent with the statement that donors arise from dislocation-related states. 12 There is no corresponding abrupt change in mobility at this thickness, which gradually decreases with decreasing thickness with values 40% greater than those obtained from single carrier model.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Such a large misfit in lattice parameters leads usually to a Stransky-Krastanov mode of growth, and thus the growth of smooth and structurally perfect films cannot be a simple matter. This is confirmed by the considerable number of papers devoted to the epitaxial growth of InSb on GaAs, where it has been found that there is no single model of the growth, and that the growth mechanism is complicated [1,2,3]. It depends on several technological parameters of the growth.…”
Section: Introductionsupporting
confidence: 56%
“…Kanisawa et al [3] recently proposed a two-stage growth, which seems to eliminate the apparent initial Stransky-Krastanov mode of growth for the case the GaAs oriented in the (111)A plane. They deposited a first 3 nm InSb layer at 310-325˚C and then, in the second stage, the rest of the film was deposited at 380-395˚C.…”
Section: Introductionmentioning
confidence: 97%